An Approach to Extracting Interschema Properties from XML Schemas at Various "Severity" Levels - De Meo, P.; Quattrone, G.; Terracina, G.; Ursino, D. (Informatica)
An Approach to Extracting Interschema Properties from XML Schemas at Various "Severity" Levels